2009
DOI: 10.2478/s11532-009-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

PbS nanostructures synthesized via surfactant assisted mechanochemical route

Abstract: PbS nanocrystals using surfactant assisted mechanochemical route has been successfully prepared. The methods of XRD, SEM, surface area and particle size measurements were used for nanocrystals characterization. The XRD patterns confirmed the presence of galena PbS (JCPDS 5-592) whatever treatment conditions were applied. The strong observable peaks indicate the highly crystalline nature in formation of PbS nanostructures where preferential crystal growth in the (200) direction after chelating agent (EDTANa 2 •… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…358,359 The XRD patterns confirmed the presence of galena PbS ( JCPDS 5-592) whatever treatment conditions were applied. The strong observable peaks in XRD patterns indicate the highly crystalline nature in formation of PbS nanostructures.…”
Section: Sulphidesmentioning
confidence: 78%
“…358,359 The XRD patterns confirmed the presence of galena PbS ( JCPDS 5-592) whatever treatment conditions were applied. The strong observable peaks in XRD patterns indicate the highly crystalline nature in formation of PbS nanostructures.…”
Section: Sulphidesmentioning
confidence: 78%
“…PbS is a luminescent material with cubic structure and has novel optical properties. 400 In bulk form, PbS has a NIR region based direct narrow band gap energy of 0.41 eV at room temperature which can be widened to a visible region of ∼2 eV by forming nanoclusters. 401 Various morphologies of PbS like NPs, 402 microflower, 403 thin-film, 404 NSs, 405 QDs, 406 and NRs 407 have been reported according to different techniques.…”
Section: Cobalt Sulfidementioning
confidence: 99%
“…PbS is a luminescent material with cubic structure and has novel optical properties . In bulk form, PbS has a NIR region based direct narrow band gap energy of 0.41 eV at room temperature which can be widened to a visible region of ∼2 eV by forming nanoclusters .…”
Section: Synthesis Biomedical Environmental and Energy Applicationsmentioning
confidence: 99%
“…It has been reported that the band gap of PbS can be widened to the visible range by forming nanoclusters. [14][15][16][17][18][19] Quite recently, the mechanochemical synthesis starting from eggshell membrane and lead acetate was used for the preparation of PbS nanocrystals. 7 To date, many synthetic methods have been reported for the preparation of PbS nanoparticles of various morphologies, such as hollow spheres, 8 wires, 9 rods, 10 tubes, 11 cubes 12 and star-like structures.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: balaz@ saske.sk; balazm@saske.sk; zorkovska@saske.sk; Fax: +421557922604; Tel: +421557922603 state high-energy milling are governed by the mechanochemical methodology. [14][15][16][17][18][19] Quite recently, the mechanochemical synthesis starting from eggshell membrane and lead acetate was used for the preparation of PbS nanocrystals. 20 The reactions occur at the interfaces of the nanometer-sized grains, which are continuously regenerated during milling.…”
Section: Introductionmentioning
confidence: 99%